Voltammetric Determination of Bromethalin by using Polymer Coated Ion Selective Bare Carbon Electrode (Global Journal of Science Frontier Research, 2017)
In this approach differential pulse adsorptive stripping voltammetric method for determination of bromethalin is reported. For improved electrode kinetics polymer coated ion selective bare carbon electrode prepared by using poly vinyl chloride (PVC) solvent membrane and tetra phenyl borate(TPB) as ion pairing agent is used as working electrode. Universal Buffer Solution with pH range 4.0-6.0 used as supporting electrolyte. The reduction product collected by using controlled potential electrolysis. Reduction mechanism is studied by cyclic voltammetry and number of electrons in rate determination step determined by using millicoulometry. Better reproducibility (98.50%) was recognized compared to the investigations by using metal electrodes. Peak currents were linear over the concentration range of 1.4x 10-8 M to 1.3×10-9 M with lower detection limit of 10-10 M. The relative standard deviation and correlation coefficients were found to be 1.15%, 0.985 respectively for 10 replicates. Calculations is made by standard addition method.
Keywords: bromethalin; differential pulse adsorptive stripping voltametric method; polymer coated ion selective electrode; universal buffer solution